Hubungan Cyberbullying Terhadap Perilaku Self Injury pada Remaja - Mudrikah Sari; Fathra Annis Nauli; Novita Kusumarini (Pusat riset dan Inovasi Nasional, 2026)
Internet use in Indonesia is highest among adolescents aged 15 to 19 years. Internet use can have a negative impact if users do not use social media appropriately, such as cyberbullying behavior. One of the impacts of cyberbullying is self injury. This study aims to determine the relationship between cyberbullying and self injury in adolescents. Methods: This studyused a descriptive descriptive correlation design with a cross sectional approach. Respondents in the study amounted to 233students of SMAN 9 Pekanbaru with sampling techniques using stratified random sampling. Cyberbullying was measured using The Cyber Victim And Bullying Scale (CVBS) questionnaire, and self injury was measured using the Self Harm Inventory (SHI). Data were analyzed using chi-square. Results: The majority adolescents have experienced cyberbullying actions moderate 153 (65.7%) and majority adolescents have experienced mild self injury 161 respondents (69.1%). Chi square analysis showed a significant relationship between cyberbullying and self injury (p = 0.000). Conclusion: There is a significant relationship between cyberbullying and self injury in adolescents. Increasing positive activities for self-development can reduce the effects of cyberbullying such as self injury.